Warming and Labile Substrate Addition Alter Enzyme Activities and Composition of Soil Organic Carbon - Tamura, Mioko; Suseela, Vidya (Frontiers in Forests and Global Change, 2021)
Warming can increase the efflux of CO2 from soils and can potentially feedback to climate change. Along with warming, the addition of labile carbon can enhance the microbial activity by stimulating the co-metabolism of recalcitrant soil organic matter. This is particularly true with soil organic carbon (SOC) under invaded ecosystems where elevated CO2 and warming may increase the biomass of invasive species resulting in higher addition of labile substrates. These labile substrates can potentially accelerate the decomposition of recalcitrant soil carbon leading to the loss of SOC. We hypothesized that the input of labile carbon would instigate a greater SOC loss with warmer temperatures compared to the ambient temperature. We also hypothesized that the temperature sensitivity of CO2 efflux would be lower in soils receiving an input of labile carbon. We investigated this by using soils from a native pine forest that received an input of labile carbon from the invasive species kudzu (Pueraria lobata). After 14 months of soil incubation, the addition of labile C through kudzu extract increased the activity of β-1,4-glucosidase compared with the control. However, the activity of N-acetyl-β -D-glucosaminidase and ergosterol (fungal biomass) decreased with labile carbon addition. The activity of peroxidase increased with warming after 14 months of soil incubation. The molecular composition of SOM indicated a general decrease in biopolymers such as cutin, suberin, long-chain fatty acids, and phytosterol with warming and an increasing trend of microbial-derived compounds with labile substrate addition. In soils that received an addition of labile C, the macro-aggregate stability was higher while the temperature sensitivity of soil C efflux was lower compared with the control. The increase in aggregate stability could enhance the physical protection of SOC from microbial decomposition potentially contributing to the observed pattern of temperature sensitivity. Our results suggest that warming could preferentially accelerate the decomposition of recalcitrant compounds while the addition of labile substrates could enhance microbial-derived compounds that are relatively resistant to further decomposition. Our study further emphasizes that global change factors such as plant invasion and climate change can differentially alter soil microbial activity and the composition of SOC.